2022
DOI: 10.1155/2022/6164614
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Nursing Teaching Curriculum Setting by Introducing Postcompetency Model under the Vision of Internet Informatization

Abstract: The nursing curriculum is to be modernized to improve the student’s skills in meeting the recent trends in medical and healthcare fields. The curriculum improvements are based on expert recommendations, authors, and informative data from different web sources. The challenging task is to improve the readability and understandability of the curriculum to real-time standards. Considering the above facts, this article introduces a refined curriculum with Internet information analysis (RC-IIA) method. The proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…These shared qualities might have been obtained from their educations, which are well stipulated within nursing curricula. It is supported by previous literature denotes that nursing curricula contain different information to improve communication skills, teamwork, skills, attitude, and knowledge [ 42 ].…”
Section: Discussionmentioning
confidence: 65%
“…These shared qualities might have been obtained from their educations, which are well stipulated within nursing curricula. It is supported by previous literature denotes that nursing curricula contain different information to improve communication skills, teamwork, skills, attitude, and knowledge [ 42 ].…”
Section: Discussionmentioning
confidence: 65%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%